Time dependent effect of indomethacin on the stimulation of protein synthesis in isolated rabbit muscle by insulin. Issue 5 (May 1986) - Palmer, R. M.; Bain, P.; Reeds, P. J.
Abstract : Insulin (100 μU/ml) stimulated protein synthesis and PGF2α release in isolated rabbit muscle, but had little effect on the rate of protein degradation. The effect of insulin persisted for at least 5 h after removal of the hormone. Indomethacin, added at the start of the incubation, inhibited the stimulatory effect of insulin on protein synthesis and PGF2α release, but did not block the binding of iodinated insulin. When added 2 h after insulin, indomethacin did not inhibit the stimulation of protein synthesis but completely inhibited the increase in PGF2α release. The results suggest that the stimulation of protein synthesis by insulin is mediated by metabolites of membrane phospholipids but that these changes are involved during the phase of response that immediately follows the binding of insulin to its receptor.